Growth Identification and Facilitation The Role of the State in the Dynamics of Structural Change - Lin, Justin Yifu (The World Bank, 2010)
Active economic policies by developing countries' governments to promote growth and industrialization have generally been viewed with suspicion by economists, and for good reasons: past experiences show that such policies have too often failed to achieve their stated objectives. But the historical record also indicates that in all successful economies, the state has always played an important role in facilitating structural change and helping the private sector sustain it across time. This paper proposes a new approach to help policymakers in developing countries identify those industries that may hold latent comparative advantage. It also recommends ways of removing binding constraints to facilitate private firms' entry into those industries. The paper introduces an important distinction between two types of government interventions. First are policies that facilitate structural change by overcoming information and coordination and externality issues, which are intrinsic to industrial upgrading and diversification. Such interventions aim to provide information, compensate for externalities, and coordinate improvements in the "hard" and "soft" infrastructure that are needed for the private sector to grow in sync with the dynamic change in the economy's comparative advantage. Second are those policies aimed at protecting some selected firms and industries that defy the comparative advantage determined by the existing endowment structure-either in new sectors that are too advanced or in old sectors that have lost comparative advantage